Follow-up of women with gestational diabetes in England. (16th November 2010) - Pierce, MB; Modder, J; Mortagy, I; Hughes, H; Springett, A; Baldeweg, S
Abstract : Women with gestational diabetes (GDM) are managed by primary and secondary care. National Institute for Health and Clinical Excellence (NICE) recommends these women have a fasting blood glucose 6 weeks postnatally (short-term follow-up), and annually thereafter (long-term follow-up). Aim: To describe the practice of consultant obstetricians and diabetologists and general practitioners (GPs) caring for women with GDM in England. Method: Postal questionnaires were sent to one obstetrician and one diabetologist in all obstetric units, and to a random 1/5 GPs in England, in 2008. Results: Response rate: 165/177 obstetricians and 164/177 diabetologists (93%) and 915/1532 (60%) GPs. Although 70% of consultants had a GDM follow-up protocol only 8% had agreed that with primary care. Short-term Follow-up: The venue for the 6-week post natal check was variable – 50% hospital, 31% GP, 17% either. 98% of consultants reported a test of glycaemic control performed 6-week post partum – 82% glucose tolerance test, 13% fasting plasma glucose. There was confusion about who was responsible for ordering this test. 89% of consultants' thought secondary care was responsible, but 44% of GPs thought that they were responsible for ordering the test. Long-term Follow-up: Only 31% diabetologists, 15% of obstetricians asked GPs to follow-up women long-term, but 39% of GPs systematically recalled these women. Conclusion: The follow-up of women with GDM is inconsistent. Responsibility for short-term follow-up and type of test to use is unclear. GPs' views accord better than consultants' with NICE guidelines. Systematic long-term follow-up is being done by a minority of GPs and not encouraged by most consultants.